Plasmonic wave at uniaxial chiral-metal-uniaxial chiral interface - Umair, M.; Ghaffar, A.; Alkanhal, A. S.; Khan, Y.; Ali, Amir (Oficyna Wydawnicza Politechniki Wrocławskiej, 2025)
This work examines the propagation of light plasmon coupling at uniaxial chiral-metal-uniaxial chiral planar interface. Gold (Au) is sandwiched between uniaxial chiral (UAC) layers. We have derived the characteristics equation by employing boundary conditions at x = d on UAC-metal and x = –d on metal-UAC interfaces. Three cases of UAC medium are discussed under the different values of chirality and core width in the visible frequency region. Based on the numerical results, it is concluded that case I (εt = –0.025ε0, εz = 0.2ε0) has the highest effective mode index (EMI), whereas case II (εt = 0.25ε0, εz = –0.2ε0) has the lowest EMI. As an additional benefit, it has also been shown that a specified frequency band can be tuned by altering the chirality and core width of the proposed planar structure. Moreover, case III (εt = –0.25ε0, εz = –0.5ε0) exhibits the highest cut-off frequency and case I exhibits the lowest value. The present work may have potential applications in optical sensors, plasmonic platforms, detectors and surface waveguides.
Optica Applicata, Vol. 55, 2025, nr 2, s. 169-179
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; plasmonics; uniaxial chiral; effective mode